Implementation of Student Facilitator Learning Model and Explaining Healthy and UnhealthyEnvironment Material to Improve Learning Activities and Learning Outcomes of Elementary School/Islamic Elementary School Students - Alifia Bilqish; Noni Putri (Journal of Contemporary Islamic Primary Education, 2024)
This study aims to determine student learning outcomes which have increased by using the SFE (Student Facilitator Explaining) model for MI/SD students. One of the recommended learning models for learning activities is the cooperative learning learning model. The cooperative learning model is a teaching and learning activity carried out in small groups, students learn and work together to arrive at optimal experiences both individual and group experiences. The method of writing scientific articles is qualitative research using descriptive methods. The results of this study regarding the application of the use of the student facilitator and explaining model in elementary schools can improve student learning outcomes by making students as facilities in learning and making students more active.